Pencatatan dan Penghitungan Skor Pada Olahraga AAIPSC dengan NFC Berbasis Android - Satria Antoni Gunawan; Silvia Rostianingsih; Alexander Setiawan (Jurnal Infra, 2019)
Recording and Calculation of Scores in AAIPSC sports requires speed and accuracy both in terms of accessing and inputting data. At this time, recording is done through paper, so the time taken to enter the calculation software takes a relatively long time. The author hopes that the application created can speed up the calculation and data can be stored to SQL server. With NFC as a validation system, it is hoped that data validation can be maintained at the time of inputting.